Dissolution and Mechanism of Tincal in Ammonium Carbonate Solutions - YILDIZ*, ADNAN; SALIH NAS†, M.; KUBILAY†, SENOL; YILMAZ†, SINAN (Asian Journal of Chemistry, 2009)
In this paper the dissolution and mechanism of tincal, sodium tetraborate decahydrate (Na2B4O7·10H2O), in ammonium carbonate solutions using the effects parameters of reaction temperature, solution concentration, solid to liquid ratio, particle size and stirring speed. The results showed that the dissolution rate increased with increasing solution concentration and reaction temperature and increased with decreasing particle size and solid to liquid ratio. It was also determined that stirring speed exerted no significant effect on dissolution rate.